Pharmacoeconomic aspects of COVID-19 treatment - I. V. Rogova; E. A. Zhidkova; I. A. Popova; A. V. Zaborovskiy; K. G. Gurevich (Фармакоэкономика)
The article provides an overview of global trends in various treatment approaches for COVID-19 in terms of pharmacoeconomic effectiveness. Different strategies for managing patients with the new coronavirus infection, separate groups of drugs are considered. The current clinical trials for COVID-19, the main directions, problems and challenges facing the healthcare system are discussed in detail. The aspects of the economic efficiency of various measures to prevent the spread of COVID-19 are presented. A thorough study of the pharmacoeconomic features of the new coronavirus infection will allow to develop effective standards for planning the process of supply for medical organizations in the pandemic.